Characterization of extracted carboxymethyl cellulose from oil palm empty fruit bunch stalk fibers for ice cream application - Muhamad Parid, Dzieda (2018)
The current extraction of carboxymethyl cellulose (CMC) from wood has created competition with wood industries. Interest in alternative sources is critical to ensure the sustainable production of CMC. Therefore, the extraction of CMC from oil palm empty fruit bunch (OPEFB) stalk fibers was evaluated. Based on previous work, highest cellulose content was obtained from raw stalk fibers with the least amount of lignin and residual oil as compared to the empty fruit bunch (EFB) and spikelet. Based on the results, OPEFB stalks fibers is suitable to be used as the substrate to produce CMC as proven by its cellulose composition (76.45%), proven morphology images, changes of diffraction patterns and new functional group occurred throughout the extraction process. Meanwhile, extracted CMC in powder form shows a good physicochemical properties in terms of its moisture content (11.18%), densities, flowability, good water retention capacity (21.55%), approaching desired colour of CMC and good physical appearance. Extracted CMC in its aqueous form also shows a comparable viscosity behaviour as it depicts a good shear thinning characteristics at 4% and the same flow behaviour curve as shown by the commercial CMC at 1% and 4% concentration. Prior to the production of the extracted CMC, the potential application of the extracted CMC from OPEFB stalk fibers were analysed on hard ice cream properties. Such data are useful in accessing the overall quality during the production and handling of hard ice cream, as well as in developing a desirable mouthfeel. The extracted CMC from OPEFB stalks fibers was able to increase the viscosity of liquid ice cream mixture (129.4cp) and hard ice cream produced by using the extracted CMC shows a good and comparable melting characteristics as it shows the same melting rate with hard ice cream produced using commercial CMC, with melting resistance (60.28%), lower overrun (35.2%) and lower hardness (28.88N) which will make the hard ice cream creamier, smoother and richer taste and the hard ice cream produced using sCMC shows a viscoelastic behaviour same as the hard ice cream produced using commercial CMC.